Minimum Wages and Excessive Effort Supply - Matthias Kräkel; Anja Schöttner (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
It is well-known that, in static models, minimum wages generate positive worker rents and, consequently, inefficiently low e?ort. We show that this result does not necessarily extend to a dynamic context. The reason is that, in repeated employment relationships, ?rms may exploit workers' future rents to induce excessively high effort.
urn:nbn:de:bvb:19-epub-13288-8
Keywords: 330; bonuses; limited liability; minimum wages; Mindestlohn; Leistungsmotivation; Arbeitsvertrag; Vertragstheorie; Theorie